2005
DOI: 10.1194/jlr.m400511-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Human paraoxonases (PON1, PON2, and PON3) are lactonases with overlapping and distinct substrate specificities

Abstract: The paraoxonase (PON) gene family in humans has three members, PON1 , PON2 , and PON3 . Their physiological role(s) and natural substrates are uncertain. We developed a baculovirus-mediated expression system, suitable for all three human PONs, and optimized procedures for their purification. The recombinant PONs are glycosylated with high-mannose-type sugars, which are important for protein stability but are not essential for their enzymatic activities. Enzymatic characterization of the purified PONs has revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
595
1
22

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 639 publications
(635 citation statements)
references
References 50 publications
17
595
1
22
Order By: Relevance
“…Interestingly, in addition to differential expression at various sites within the host (PON1 and PON3 are expressed in the liver and sera, whereas PON2 is a cell-associated enzyme expressed in various tissues [103]), the different PON enzymes appear to have unique enzymatic activities. All three purified PONs had AHL lactonase activity in vitro, but each enzyme was determined to have a distinct specificity against a range of substrates, with PON1 and PON3 acting on the widest range of substrates but PON2 being the most active against AHLs (76,(103)(104)(105). In vitro results have supported a role for PON2 in AHL degradation by murine tracheal epithelial cells (104), and other experiments have demonstrated that both serum PON1 and purified PON1 reduce P. aeruiginosa biofilm formation in vitro (103).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 53%
See 1 more Smart Citation
“…Interestingly, in addition to differential expression at various sites within the host (PON1 and PON3 are expressed in the liver and sera, whereas PON2 is a cell-associated enzyme expressed in various tissues [103]), the different PON enzymes appear to have unique enzymatic activities. All three purified PONs had AHL lactonase activity in vitro, but each enzyme was determined to have a distinct specificity against a range of substrates, with PON1 and PON3 acting on the widest range of substrates but PON2 being the most active against AHLs (76,(103)(104)(105). In vitro results have supported a role for PON2 in AHL degradation by murine tracheal epithelial cells (104), and other experiments have demonstrated that both serum PON1 and purified PON1 reduce P. aeruiginosa biofilm formation in vitro (103).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 53%
“…CHO cells expressing any of the murine PON genes were able to degrade 3OC12HSL at levels comparable to those in cells expressing the known AHL lactonase gene aiiA (102), and treatment of serum with PON inhibitors reduced 3OC12HSL degradation (103). Evolutionary relationship analysis of PONs and studies of PON1 reactivity with more than 50 different substrates demonstrated that PON1 can hydrolyze lactones, esters, and phosphotriesters using the same active site, but its primary activity appears to be as a lactonase (76,77). Interestingly, in addition to differential expression at various sites within the host (PON1 and PON3 are expressed in the liver and sera, whereas PON2 is a cell-associated enzyme expressed in various tissues [103]), the different PON enzymes appear to have unique enzymatic activities.…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…Protective HDL function is primarily via the enzyme paraoxonase 1 (PON1) which hydrolyzes lipid peroxides in human atherosclerotic lesions (31)(32)(33). PON1 has a common coding region polymorphism, a glutamine (Q) to arginine (R) substitution at position 192, which is associated with a number of pathophysiological conditions such as CVD and some others (31).…”
Section: Discussionmentioning
confidence: 99%
“…4 In this context, the levels of PON1, which acts as lactonase as well as an antioxidant, could play an important role as a protective agent against the deleterious effect of elevated Hcys. The physiological substrate of PON1 is unknown, 21 and measurements of PON1 activity are done by monitoring the rates of hydrolysis of exogenous substrates such as phenylacetate and paraoxon, although this may not quantify the degree of the antiatherogenic or antioxidant potential of PON1. As a strong correlation between the PON1 levels assessed by ELISA and the PON1 activity measurements has been reported, PON1 activity measurements qualify as markers for PON1 levels in serum as reported by Himbergen et al 22 In this study, the PON1 activity is measured in terms of its ARE activity using phenylacetate as the substrate.…”
Section: Discussionmentioning
confidence: 99%